Advantages and Disadvantages of the Deductive Method - Qoʻchqorova Zulfizar Abduxamid qizi; Axmadaliyeva Muslima Anvarjon qizi (Journal of Innovation in Education and Social Research, 2023)
The deductive method, a cornerstone in logical reasoning, possesses both advantages and disadvantages. On the positive side, it offers a structured approach, starting from general principles to specific conclusions, fostering clarity and precision. This method often produces reliable results when the initial premises are accurate. However, its rigidity may limit creativity and overlook nuances, and if the initial assumptions are flawed, it can lead to erroneous conclusions. Striking a balance between deductive reasoning's structured framework and the need for flexibility is crucial for maximizing its benefits.